“TÁRBIYA” PÁNIN OQÍTÍWDA ZAMANAGÓY DIDAKTIKALÍQ TEXNOLOGIYALAR - Meńlibaeva, A.O. (SCIENCE and SOCIETY, 2025)
The article describes the use of modern didactic technologies in teaching the subject of “Upbringing” and its importance in a wide range. The lessons are related to what modern didactic technologies should be used. The article is a practical profession for teachers who correct lessons, ensure student activity and implement educational tasks based on modern requirements.
Keywords: modern didactic technologies; communicative competence; interactive methods; gemification; multimedia materials; the effectiveness of the educational process; experiments